Dynamic glucose‐enhanced (DGE) MRI in the human brain at 7 T with reduced motion‐induced artifacts based on quantitative R1ρ mapping. Issue 1 (1st December 2019) - Boyd, Philip S.; Breitling, Johannes; Zimmermann, Ferdinand; Korzowski, Andreas; Zaiss, Moritz; Schuenke, Patrick; Weinfurtner, Nina; Schlemmer, Heinz‐Peter; Ladd, Mark E.; Bachert, Peter; Paech, Daniel; Goerke, Steffen
Abstract : Purpose: Dynamic glucose‐enhanced (DGE)‐MRI based on chemical exchange‐sensitive MRI, that is, glucoCEST and gluco‐chemical exchange‐sensitive spin‐lock (glucoCESL), is intrinsically prone to motion‐induced artifacts because the final DGE contrast relies on the difference of images, which were acquired with a time gap of several mins. In this study, identification of different types of motion‐induced artifacts led to the development of a 3D acquisition protocol for DGE examinations in the human brain at 7 T with improved robustness in the presence of subject motion. Methods: DGE‐MRI was realized by the chemical exchange‐sensitive spin‐lock approach based either on relaxation rate in the rotating frame (R1ρ )‐weighted or quantitative R1ρ imaging. A 3D image readout was implemented at 7 T, enabling retrospective volumetric coregistration of the image series and quantification of subject motion. An examination of a healthy volunteer without administration of glucose allowed for the identification of isolated motion‐induced artifacts. Results: Even after coregistration, significant motion‐induced artifacts remained in the DGE contrast based on R1ρ ‐weighted images. This is due to the spatially varying sensitivity of the coil and was found to be compensated by a quantitative R1ρ approach. The coregistered quantitative approach allowed the observation of a clear increase of the DGE contrast in a patient with glioblastoma, which did not correlate with subject motion. Conclusion: The presented 3D acquisition protocol enables DGE‐MRI examinations in the human brain with improved robustness against motion‐induced artifacts. Correction of motion‐induced artifacts is of high importance for DGE‐MRI in clinical studies where an unambiguous assignment of contrast changes due to an actual change in local glucose concentration is a prerequisite.